Sport Education model and orienteering.Efects on adolescent students’ life satisfaction, multiple intelligences, basic psychological needs and curricular model’s perceptions. - Puente-Maxera, F.; Méndez-Giménez, A.; Martínez de Ojeda Pérez, D.; Liarte Belmonte, J. P. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The aim of this study was to assess the effects of a Sport Education (SE) model-based teaching unit through orienteering on grade 9 (14-17 years) students’ life satisfaction, multiple intelligences, basic psychological needs and curricular model perceptions.81 students (Mage = 14.62; SD = .80) allocated in three intact groups from a high-school in Region of Murcia (Spain), took part in this unit. Based on a quasi-experimental design (pretest-posttest measures), data were collected from interviews (teacher perspective) and both quantitative and qualitative questionnaires (student perspective). Significant improvements were obtained on the development of the three main SE goals (competency, literacy and enthusiasm), whereas no significant changes were found on life satisfaction and multiple intelligences. Findings confirmed orienteering as a suitable content to be taught according through the pedagogical principles of SE model.Likewise, results showed its benefits on the development of the objectives this pursues.